Hydatid cyst fluid promotes peri-cystic fibrosis in cystic echinococcosis by suppressing miR-19 expression. Issue 1 (December 2016) - Zhang, Chuanshan; Wang, Limin; Ali, Tuergan; Li, Liang; Bi, Xiaojuan; Wang, Junhua; Lü, Guodong; Shao, Yingmei; Vuitton, Dominique; Wen, Hao; Lin, Renyong
Abstract Background Echinococcus granulosus infection causes cystic echinococcosis (CE); the generation of liver fibrosis around the parasitic larval cyst (metacestode) may play a major role in the spontaneous limitation of the parasitic growth; however, fibrogenesis has received little attention in CE. It has been reported that miR-19b plays a role in various diseases, including infectious diseases, by regulating fibrogenesis. However, its function in the development of liver fibrosis inE. granulosus infection is unknown. Methods The expression of miR-19b and genes that are involved in liver fibrosis were analysed inE. granulosus -infected human livers using qRT-PCR. The role of miR-19b on hepatic stellate cells (LX-2 cells in vitro) treated with hydatid cyst fluid (HCF) was then analysed by 3-(4, 5-dimet-hylthiazol-2-yl)-2, 4-diphenyl-tetrazolium bromide (MTT) assay, qRT-PCR, Western blot and flow cytometry. Results The results showed that the expression of miR-19 was significantly reduced in the pericystic collagen-rich liver tissue of CE patients, compared to normal liver. Incubation of LX-2 cells (in vitro) with HCF induced a decreased proliferation of these cells and a reduced expression of miR-19, inversely correlated with the expression of collagen 1A1 and TGF-β receptor II (TβRII). Conversely, overexpression of miR-19 by LX-2 cells inhibited the proliferation of these cells and led to decreased TβRII expression. Conclusions Our study provides new evidence for the intervention of miRNAs in the regulation of fibrosis in infectious diseases; it suggests thatE. granulosus can inhibit miR-19 liver expression and promote fibrosis through the increase in TβRII, the activation of hepatic stellate cells and extracellular matrix production.